Moving Bedforms Control CO2 Production and Distribution in Sandy River Sediments. Issue 4 (17th April 2023) - Schulz, H.; Teitelbaum, Y.; Lewandowski, J.; Singer, G. A.; Arnon, S.
Abstract: Streams and rivers play an important role in the global carbon cycle. The origins of CO2 in streams are often poorly constrained or neglected, which is especially true for CO2 originating from heterotrophic metabolism in streambeds. We hypothesized that sediment movement will have a direct effect on stream metabolism, and thus, the aim of this study was to quantify the effect of moving bedforms on the production of CO2 in sandy streambeds. We conducted flume experiments where we used planar optodes to measure the distributions of O2 and CO2 under various streambed celerities. We combined these measurements with an assessment of bed morphodynamics and modeling to calculate O2 consumption and CO2 production rates. Our results indicate that sediment transport can strongly influence streambed metabolism and CO2 production. We found that bedform celerity controls the shape of the hyporheic zone and exchange flux, and is directly linked to the spatial and temporal distributions of O2 and CO2 . It was also found that the most pronounced change in CO2 production occurred when the bed changed from stationary conditions to a slowly moving bed. A more gradual increase in O2 consumption and CO2 production rates was observed with further increase in celerity. Our study also points out that bedform movement causes hydraulic isolation between the moving and the non‐moving fraction of the streambed that can lead to a transient storage of CO2 in deeper sediments, which may be released in bursts during bed scour. Plain Language Summary: Streams play an important role in the global carbon cycle. Carbon is transported in streams and rivers toward the oceans, stored in the streambed, or emitted as the greenhouse gas CO2 to the atmosphere. Many studies try to link CO2 in streamwater and CO2 emission to flow conditions and CO2 import via groundwater while ignoring the role of microbial processes in sediments that also produce CO2 . We performed lab experiments using an artificial stream channel and special sensors in the streambed to investigate the influence of moving sandy sediments on the distribution and production of CO2 . We found that sediment movement controls the distribution of CO2, and that those distributions are influenced by the flow paths of the water flowing through the sediment. We also found that the production of CO2 and the flux of stream water entering the sediment increased with the speed of the sediment movement. Moreover, our results point out that the movement of the sediment disconnects the lower, non‐moving part of the sediment from the upper, moving part of the sediment. This can build up a storage of high CO2 concentrations in the deeper sediment, which may be released as bursts during events of streambed erosion. Key Points: Bedform celerity controls the spatial and temporal distribution of CO2 in stationary and moving sandy bedforms Production of CO2 in sediments increases abruptly as the bed starts to move and more gradually with increasing bedform celerity Bedform movement causes isolation of the non‐moving fraction of the streambed and increase in transient storage of CO2 in deeper sediments